PENGEMBANGAN USAHA TEMPE DAN KERIPIK TEMPE UNTUK UKM JATISRONO WONOGIRI - Agustina Intan Niken Tari; Tri Wiharti; Sri Sri Hartati (LPPM UNS, 2015)
The IbM aims at improving the ability of management SME I (Saikem SMEs ) and SME II (Satino SMEs) in making tempe and tempe chips in Jatisrono Wonogiri. The improvement of management capabilities are: ability to produce products with sanitation and food safety, packaging and labeling as well as bookkeeping. Evaluation and indicator for both SMEs in this program include (1) increasing participant's knowledge of the theories that have been given about the product tempe and tempe chips (2) increasing the participant’s skills towards the introduction of tools and assistance on the application of sanitary and food safety packaging and labeling as well as capability of bookkeeping. Pretest result is globally as follows : Saikem SMEs = 66.67 , Satino SMEs = 70 and average = 68.34. Post test results for both SMEs has average = 100. The improvement of knowledge for Saikem SMEs is 49,93 % and for Satino SMEs is 42.86% or the is average= 46.40 %.. The Performance of IbM”s tool assistance for Saikem SMEs is 5 Kg / min (form of soy husk peeler), while that of Satino SMEs is 15 slices of tempe with an average of thickness of 0.2 cm for the tempe chopper. Average production of tempe on SaikemSMEs after soy husk peeler has been given is 27.5 % , while the production of tempe chips SatinoSMEs after tempe chopper has been given is 25 % . Both SMEs (Saikem SMEs and Satino SMEs) are able to perform the bookkeeping..